Profession: consultant - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Profession: consultant," by Robert Lescarbeau, Maurice Payette and Yves St-Arnaud.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z